PENAMBAHAN TULANGAN LONGITUDINAL DENGAN KOMPOSIT MORTAR SEBAGAI ALTERNATIF PERKUATAN LENTUR PADA BALOK BETON BERTULANG - Nursiah Chairunnisa (Universitas Lambung Mangkurat, 2009)
In order to maintain efficient serviceability structure cause change of function from structures likes overloading or lack of quality control at construction , structures must be strengthened so they can to fulfill the code of structures built to day and future. One of method to strengthenned of structures elements was beams elements. This research had to know about effectiveness strengthening methods of reinforced concrete beams using longitudinal compression and tension reinforcement with jacketing mortar as flexural strengthening and had to know about implementation for mortar that had high flowability.In this research specimen models consist of four specimens: one was control beam (BK), one was monolith beam (BM) and one was strengthened beam (BP) . All beams were tested under 2-point loading midspan as flexural load and also instrumented for the measurement of mid-span deflection and crack pattern.The result show that monolith and strengthened beams have performed better in the ultimate load for BM specimen were 124,79% , BP specimen were 75,49% compared BK specimen. Ductility of beam at experiment for BM specimen decrease were 55,78% compared BK , ductility of BP specimen increased were 50,61% compared BK specimen because of debonding . Failure patterns of the control beam (BK) and monolithical beam (BM) were flexural while the strengthened beam (BP) had debonding. At this researched, methods of strengthened reinforced concrete beam with mortar jacketing had simply worked for implementation.